2017
DOI: 10.1080/15287394.2017.1420505
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxicity properties of Copaifera multijuga oleoresin and its chemical marker, the diterpene (−)-copalic acid

Abstract: 2-AA, 2-anthramine; 2-AF, 2-aminofluorene; AFB, aflatoxin B; B[a]P, benzo[a]pyrene; BOD, biological oxygen demand; BPDE, benzo[a]pyrene-7,8-diol-9,10-epoxide; CA, (-)-copalic acid; CMO, oleoresin of Copaifera multijuga, DMEM, Dulbecco`s Modified Eagles`s Medium; DMSO, dimethylsulfoxide; EMBRAPA, Brazilian agricultural research corporation; GC-MS, gas chromatography-mass spectrometry; HAM-F10, nutrient mixture F-10 Ham; HPLC, high performance liquid chromatography; LC-MS, liquid chromatography-mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 67 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…The data obtained showed that none of them exert no genotoxic/mutagenic effect under the experimental conditions employed. When compared to our results, these data indicate that for C. multijuga both the extract, which was evaluated in our study, and oleoresin, as evaluated by Alves et al [13], do not affect the number of revertant colonies compared to the negative control in Ames test; the same applies to copalic acid and kaurenoic acid. These findings suggest that mutagenicity is absent, regardless of metabolic activation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The data obtained showed that none of them exert no genotoxic/mutagenic effect under the experimental conditions employed. When compared to our results, these data indicate that for C. multijuga both the extract, which was evaluated in our study, and oleoresin, as evaluated by Alves et al [13], do not affect the number of revertant colonies compared to the negative control in Ames test; the same applies to copalic acid and kaurenoic acid. These findings suggest that mutagenicity is absent, regardless of metabolic activation.…”
Section: Discussionsupporting
confidence: 82%
“…In this way, the oleoresin of C. multijuga and its chemical marker, diterpene copalic acid, were evaluated by Alves et al [13] through the micronucleus assay (V79 cell) and the Ames test for in vitro study, as well as micronucleus and comet assays (Swiss mice) for in vivo assay. The data obtained showed that none of them exert no genotoxic/mutagenic effect under the experimental conditions employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation